La inconstancia de la suerte (¿1700-1800?), Herodotus and Fortune: notes on an anonymous «comedia histórica» - Marino, Giuseppe (Cuadernos de Ilustración y Romanticismo, 2023)
La inconstancia de la suerte (Biblioteca Nacional de España, mss. 16216) is a manuscript that has never been studied before, and its author and composition date remain unknown. It is a historical play that includes one of the most represented topics by dramatists during the Spanish Golden Age, that of Fortuna bifrons. Intending to teach a moral lesson, the author of this comedy intermingled his characters, both historical and imaginary, framing their life trajectories around having experienced prosperous then adverse fortune, and vice versa. This bilogy was generated from a well-known paradigm in our literature, first found in The Histories by Herodotus, namely the war between the king of Persia, Cyrus, and the king of Lydia, Croesus, and the famous dialogue between Solon, one of the seven sages of Greece, and the Lydian monarch on happiness and variability of luck. This study aims to shed light on this codex and its author, likely Antonio Valladares de Sotomayor (1737-1820), through a multidisciplinary perspective that encompasses ecdotic, historical, narrative and linguistic aspects in order to clarify its origin and place it correctly in the history of Spanish literature.